2002
DOI: 10.4049/jimmunol.169.6.2813
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: Fyn Is Essential for Tyrosine Phosphorylation of Csk-Binding Protein/Phosphoprotein Associated with Glycolipid-Enriched Microdomains in Lipid Rafts in Resting T Cells

Abstract: In resting T cells, Csk is constitutively localized in lipid rafts by virtue of interaction with a phosphorylated adaptor protein, Csk-binding protein (Cbp)/phosphoprotein associated with glycolipid-enriched microdomains, and sets an activation threshold in TCR signaling. In this study, we examined a kinase responsible for Cbp phosphorylation in T cell membrane rafts. By analyzing T cells from Fyn−/− mice, we clearly demonstrated that Fyn, but not Lck, has its kinase activity in membrane rafts, and plays a cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
112
4

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(124 citation statements)
references
References 19 publications
8
112
4
Order By: Relevance
“…The involvement of Cbp in reducing Lyn kinase activity after Epo stimulation of immature erythroid cells, complements studies showing inactivation of Src and Fyn in other cell types (47)(48)(49). The crucial role of recruiting Csk/Ctk by Cbp Tyr 314 was also demonstrated in erythroid cells.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…The involvement of Cbp in reducing Lyn kinase activity after Epo stimulation of immature erythroid cells, complements studies showing inactivation of Src and Fyn in other cell types (47)(48)(49). The crucial role of recruiting Csk/Ctk by Cbp Tyr 314 was also demonstrated in erythroid cells.…”
Section: Discussionsupporting
confidence: 53%
“…The data presented here detail how Lyn, like Src and Fyn, is negatively regulated by Cbp (30,31,47,48). The involvement of Cbp in reducing Lyn kinase activity after Epo stimulation of immature erythroid cells, complements studies showing inactivation of Src and Fyn in other cell types (47)(48)(49).…”
Section: Discussionmentioning
confidence: 49%
“…However, the regulation of phosphorylation of PAG is not well understood. Previous studies indicated that Fyn, but not Lck, is predominantly responsible for the phosphorylation of PAG in resting peripheral T cells (44). Interestingly, although one study suggested that CD45 phosphatase could act on Tyr 371 of PAG (45), another failed to confirm this finding (15).…”
Section: Slp-76 Y3f Is Sufficient To Replicate the Majority Of Phosphcontrasting
confidence: 38%
“…It was already shown that Cbp can be a target of SFK (8-10), but it remained unclear whether there are specificities among the SFK members. Previous analysis showed that phosphorylation of Cbp is substantially down-regulated in the immune system of Fyn-deficient mice (37), suggesting the potential role of Fyn in Cbp phosphorylation. To further verify this finding, we analyzed the raft fraction in neonatal brains of Fyn-deficient mice.…”
Section: Localization Of Sfk In Lipid Rafts and Cbp Phosphorylation Imentioning
confidence: 99%